2018
DOI: 10.1080/14767058.2018.1454422
|View full text |Cite
|
Sign up to set email alerts
|

Colostrum and mature breast milk analysis of serum irisin and sterol regulatory element-binding proteins-1c in gestational diabetes mellitus

Abstract: Low irisin and SREBP1-c levels may favor development of GDM in pregnant subjects. Further, low mature breast milk levels may act as a continued stressor from fetal to infant life as long as breast-feeding is continued. Further studies are required to identify the mechanistic relationship between these biomarkers and GDM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…Salusin-alpha and -beta levels were lower in colostrum of women with GDM [23]. SREBP1-c profile showed a level reduced from a very low value to an undetectable range in colostrum and mature breast milk, respectively [21].…”
Section: Hormonesmentioning
confidence: 90%
See 2 more Smart Citations
“…Salusin-alpha and -beta levels were lower in colostrum of women with GDM [23]. SREBP1-c profile showed a level reduced from a very low value to an undetectable range in colostrum and mature breast milk, respectively [21].…”
Section: Hormonesmentioning
confidence: 90%
“…Irisin concentrations, analyzed in two studies, were accordingly found to be low in GDM subjects in the colostrum and transitional milk [21,22]. In mature milk, Fatima et al observed a reduction in concentrations, not confirmed by Aydin et al [21,22].…”
Section: Hormonesmentioning
confidence: 94%
See 1 more Smart Citation
“…Unsurprisingly, the breast milk of the GDM patients had lower concentrations of irisin that of the control group, regardless of colostrum or mature milk [ 140 ]. Additionally, Fatima et al speculated that unfavorable effects on health and lipid regulation may stem from continuous feeding of breast milk with fewer irisin [ 144 ]. The remarkable connection between low irisin levels in breast milk and infant weight require further investigation.…”
Section: Clinical Applications Of Adipokines Measurements In Variomentioning
confidence: 99%
“…The composition of human milk depends on many factors (e.g., period of the milk, time of day when milk is obtained, mother’s nutritional status, and age of the newborn; Dritsakou, Liosis, Valsami, Polychronopoulos, & Skouroliakou, 2018). Human milk is divided into three basic categories according to the period of secretion and composition: colostrum (milk secreted for the first 5 days after birth [postpartum]), transitional milk (milk secreted between 5 and 15 days after colostrum [transitional]) and mature milk (milk secreted after the 15th day [mature]; Fatima, Khalid, Ladak, & Ali, 2018). Although the nutritional content of these varieties of milk differ, the content generally varies according to the physiological needs of the child (Mazurier et al, 2017; Aydin, 2018).…”
Section: Introductionmentioning
confidence: 99%